Solusi Perselisihan Konsulat Jenderal dan Kedutaan Besar Amerika Serikat di Indonesia dengan Staf Warga Negara Indonesia - Eunike Giovani Fernanda; Ida Bagus Oka Ana (Lentera Hukum, 2018)
Indra Taufiq, an Indonesia citizen, a former local staff working for the United States of America Consulate General in Medan, brought an appeal to the Indonesian Supreme Court to the United States of America Consulate General in Medan and its embassy to pay Indra Taufiq’s termination of employement rights. Although the verdict of the cassation was won by Indra Taufiq, the consulate general and the embassy of the United States of America refused to carry out the court's verdict on the grounds of diplomatic immunity. This is a legal issue that should be reviewed in terms of the perspective of international law related to the legal status of diplomatic or consular representation in Indonesia and what should be done Indonesia to protect the rights of Indonesian citizens workers. Keywords: Diplomatic and Consular Immunity, Dispute, Citizens